How to market to people not like you : "know it or blow it" rules for reaching diverse customers - McDonald, Kelly. 1961- (Hoboken, N.J. : Wiley, 2011)
"Reach new and diverse customer groups and expand your market share The standard approach to marketing is to look for as many people as possible who fit one core customer profile. How to Market to People Not Like You challenges this traditional thinking about core customer bases, giving you a new approach to expand your customer base and your business. Arguing for focusing on customer values rather than demographics, How to Market to People Not Like You reveals how you can grow business and profits by targeting those who are different from your core audience, rather than those who share similarities. Reach unfamiliar new market segments with your products Learn how to engage micro-segmented customer groups Author's company was named one of the top ad agencies in the US by Ad Age Find out How to Market to People Not Like You, understand the needs and values that distinguish diverse customers, and reach their hearts, minds, and wallets."--
Includes index.
Keywords: Marketing; Consumer satisfaction